Violence, exclusion and resilience among Ivoirian travestis. Issue 1 (2nd January 2017) - Thomann, Matthew; Corey-Boulet, Robbie
Abstract : Among sexual and gender minorities in Côte d'Ivoire, travestis are defined as individuals born anatomically male who live as women on a full- or part-time basis. Travestis encounter harsher stigmatization and violence than sexual minorities whose gender normativity allows them to avoid unwanted attention. Moreover, they have traditionally been underserved by Ivoirian sexual minority rights groups, who have worked to distance themselves from travestis, framing them as recklessly indiscreet. In this paper, we examine the extent to which travestis' isolation has lessened in the wake of the post-election violence that followed Côte d'Ivoire's 2010 presidential election. We trace how Ivoirian travestis became increasingly vulnerable following the installation of a new national army that proved more hostile to them. And we show how, as a result of anti-travesti abuses committed by the army, non-travesti sexual minority activists became increasingly aware of the plight of travestis, and took steps to include them in their programming. These activists may have also been motivated by an increasing interest in transgender issues on the part of international donors. Finally, we explore the extent to which emerging human rights and HIV/AIDS programming has resulted in newly embodied positions for travestis as they confront identifications reflecting Western trans-spectrum identities.